Analysis of the Implementation of National Education Standards by Principals of Madrasah Aliyah Negeri - Fakhri, Jamal; Yetri, Yetri; Saputra, Muhammad Indra; Hasanah, Uswatun; Sugiharta, Iip (Universitas Islam Negeri Raden Intan Lampung, 2024)
This research aims to analyze the competencies of Madrasah Principals in implementing the National Education Standards (NES at Madrasah Aliyah Negeri (MAN) in Bandar Lampung. The study adopts a qualitative approach using data collection methods such as interviews, documentation, observations, and Focus Group Discussions (FGD). The research focuses on assessing the principals' competency in managing the eight components of the SNP, including Graduate Competency Standards, Content Standards, Process Standards, and Assessment Standards. The findings reveal that MAN 1 has fully complied with the SNP criteria for the majority of the standards, with the principal’s competency categorized as